2023
DOI: 10.3390/ijerph20021331
|View full text |Cite
|
Sign up to set email alerts
|

The Potential Environmental and Social Influence of the Inorganic Salt Hydrates Used as a Phase Change Material for Thermal Energy Storage in Solar Installations

Abstract: The aim of this article is to assess the potential impact of inorganic salt hydrates used as PCM material in solar installations on the environment and human health and to assess the society’s approach to this technology. The properties of salt are discussed in two ways: first, by analyzing the environmental and health problems caused by chemical hazards on the basis of the available material safety data sheets. Secondly, by analyzing the potential disadvantages of salt hydrates in terms of environmental hazar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 61 publications
0
6
0
Order By: Relevance
“…At present, global carbon dioxide emissions have reached record levels and represent one of the most serious global environmental challenges. For this reason, if there is an opportunity to reduce carbon dioxide emissions by reducing the amount of sludge incinerated while recovering a valuable raw material, it is vital that this potential is fully exploited [39].…”
Section: Element Mobility Ratio (Emr)mentioning
confidence: 99%
“…At present, global carbon dioxide emissions have reached record levels and represent one of the most serious global environmental challenges. For this reason, if there is an opportunity to reduce carbon dioxide emissions by reducing the amount of sludge incinerated while recovering a valuable raw material, it is vital that this potential is fully exploited [39].…”
Section: Element Mobility Ratio (Emr)mentioning
confidence: 99%
“…Mahdi et al evaluated paraffin wax as a PCM, focusing on its thermal storage capabilities ( Mahdi et al, 2019 ). Nartowska et al underscored the potential of sodium dihydrogen phosphate dodecahydrate as an eco-friendly and cost-effective PCM for solar devices ( Nartowska et al, 2023 ). Wang et al demonstrated that pairing foam aluminum with paraffin improves the PCM’s thermal conductivity ( Wang et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…The thermal conductivity coefficient can be from several (0.25% CaCO 3 (50:50%)/DI [15] or 0.3% Fe 3 O 4 -CNT/water [16]) to even several dozen percents higher (1% TiO 2 + MWCNT/EG [17] and 1.5% Al 2 O 3 + MWCNT/thermal oil [9]) than in the case of the base liquid. Nanofluids are also eagerly tested in closed-loop solar systems [18], in which solar radiation energy is converted into thermal [19] or electrical energy [20]. The efficiency of exchanger installations can be effectively determined using the exergy method, as in, for example, [21][22][23].…”
Section: Introductionmentioning
confidence: 99%